The role of agro-input dealer certification in promoting sustainable pest control: insights from Uganda - Tambo, Justice A; Holmes, Keith A.; Aliamo, Caroline; Mbugua, Fredrick; Alokit, Christine; Muzira, Fred; Byamugisha, Andrew; Mwambu, Paul (Taylor & Francis Group, 2024)
ABSTRACTPesticides are crucial for increasing agricultural productivity, but they have also beenlinked to a range of health and environmental risks. In this paper, we used nationallyrepresentative data from 557 agro-dealers in Uganda to assess the role of agro-dealercertification in improving knowledge and practices related to environmentally-friendly pest control. We found that almost half of the sampled agro-dealers werenot certified or accredited by regulatory bodies, even though this is a prerequisitefor selling pesticides in the country. Results further showed that only 16% of theagro-input shops were selling biopesticide products, largely due to a lack ofawareness, access and demand from farmers. Regression results showed thatcertified agro-dealers were 9–12 percentage points more likely to know aboutbiopesticides and integrated pest management, and 8–10 percentage points morelikely to sell biopesticide products, compared to their non-certified counterparts.Ourfindings imply that agro-dealer certification courses can play an important rolein raising knowledge and stimulating the supply of environmentally-benign pestcontrol products. We identified regulatory enforcement, a decentralizedcertification system and agro-dealer associations as some of the potentialpathways for incentivising compliance with certification requirements, therebypromoting lower-risk pest control products and strategies
Keywords: Agro-input dealers;certification; biopesticides;integrated pestmanagement; Uganda